Commodity Price Shocks and the Business Cycle: Structural Evidence for the U.S. - Matthias Gubler; Matthias S. Hertweck (University of Basel, Center of Business and Economics (WWZ), 2011)
This paper develops a 9-dimensional SVAR to investigate the sources of the U.S. business cycle. We extend the standard set of identified shocks to include unexpected changes in commodity prices. Our main result is that commodity price shocks are a very important driving force of macroeconomic fluctuations, second only to investment-specific technology shocks. In particular, we find that commodity price shocks explain a large share of cyclical movements in inflation. Neutral technology shocks and monetary policy shocks seem less relevant at business cycle frequencies. The impulse response dynamics provide support for medium-scale DSGE models, but not for strong price rigidities.
Keywords: C32; E32; E52; Q43; 330; business cycles; commodity price shocks; structural VAR; Rohstoffpreis; Schock; Wirkungsanalyse; Konjunktur; VAR-Modell; Schätzung; USA